2010
DOI: 10.1074/jbc.m109.091660
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Factor/Splicing Factor 2 Regulates the Expression of the ζ Subunit of the Human T Cell Receptor-associated CD3 Complex

Abstract: T cells from patients with systemic lupus erythematosus express decreased levels of the T cell receptor-associated CD3 chain, a feature directly linked to their aberrant function. The decrease in CD3 protein expression is in part due to decreased levels of functional wild type isoform of the 3-untranslated region (UTR) of CD3 mRNA with concomitant increased levels of an unstable alternatively spliced isoform. In order to identify factors involved in the post-transcriptional regulation of CD3, we performed mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 42 publications
2
59
0
Order By: Relevance
“…The TCR-associated CD3ζ chain expression is decreased in T cells from patients with SLE (8). Moreover, we previously showed that SF2/ASF regulates the expression of the CD3ζ chain in human T cells (13). Here we asked whether SF2/ASF expression is altered in patients with SLE.…”
Section: Sf2/asf Expression Levels Are Decreased In T Cells From Patimentioning
confidence: 99%
See 2 more Smart Citations
“…The TCR-associated CD3ζ chain expression is decreased in T cells from patients with SLE (8). Moreover, we previously showed that SF2/ASF regulates the expression of the CD3ζ chain in human T cells (13). Here we asked whether SF2/ASF expression is altered in patients with SLE.…”
Section: Sf2/asf Expression Levels Are Decreased In T Cells From Patimentioning
confidence: 99%
“…Alternative splicing of the CD45 isoforms was shown to be regulated by SF2/ASF using a minigene model system (24). We recently showed that SF2/ASF regulates the alternative splicing of the CD3ζ 3′UTR in primary human T cells (13). However, the role of SF2/ASF in human T lymphocyte function and specifically in autoimmune disease has never been studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SDS-PAGE and Immunoblotting-Whole T cell lysates obtained from SLE patients and healthy controls were analyzed by SDS-PAGE and subsequent immunoblotting as described previously (17). Phosphorylated SP-1 protein was visualized using an anti-SP-1 antibody kindly provided by B. KahnPerles (Marseille, France (18)) that specifically detects SP-1 phosphorylated at its serine 59.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a previous report has demonstrated that CD3 chain mRNA in T cells exists as two isoforms: a full sequence form and a specific 3Ј UTR-deleted form that influences mRNA stability, leading to mRNA degradation (43). Interestingly, we have evidence that ectopic expression of NSrp70 reduces the expression of the CD3 chain in Jurkat T cells.…”
Section: Discussionmentioning
confidence: 50%